Robotic arm controller using computer interfacing - Ramliy, Mohamad Yusri (2006)
This project is about to develop a robotic arm controller by using computer interfacing. The technique uses the capabilities of the computer's parallel port to provide an 8-bit input. The software that is use to provides the interface is Microsoft Visual Basic. The scope of this project is to control the robotic arm to pick the specified object and move it to the specified angle or direction. At the end of this project, the robotic arm finally can be operated by itself automatically at actual job just by clicking on one switch or button. In this project, ROB 3 – EUROBTEC was used to interface with the programming.